Time to onset of cannabidiol treatment effect and resolution of adverse events in tuberous sclerosis complex: Post hoc analysis of randomized controlled phase 3 trial GWPCARE6. Issue 5 (4th March 2022) - Wu, Joyce Y.; Cock, Hannah R.; Devinsky, Orrin; Joshi, Charuta; Miller, Ian; Roberts, Colin M.; Sanchez‐Carpintero, Rocio; Checketts, Daniel; Sahebkar, Farhad
Abstract: Objective: To estimate the timing of cannabidiol (CBD) treatment effect (seizure reduction and adverse events [AEs]) onset, we conducted a post hoc analysis of GWPCARE6 (NCT02544763), a randomized, placebo‐controlled, phase 3 trial in patients with drug‐resistant epilepsy associated with tuberous sclerosis complex (TSC). Methods: Patients received plant‐derived pharmaceutical formulation of highly purified CBD (Epidiolex; 100 mg/ml oral solution) at 25 mg/kg/day (CBD25) or 50 mg/kg/day (CBD50) or placebo for 16 weeks (4‐week titration, 12‐week maintenance). Treatment started at 5 mg/kg/day for all groups and reached 25 mg/kg/day on Day 9 and 50 mg/kg/day on Day 29. Percentage change from baseline in TSC‐associated seizure (countable focal or generalized) count was calculated by cumulative day (i.e., including all previous days). Time to onset and resolution of AEs were evaluated. Results: Of 224 patients, 75 were randomized to CBD25, 73 to CBD50, and 76 to placebo. Median (range) age was 11.3 (1.1–56.8) years. Patients had discontinued a median (range) of 4 (0–15) antiseizure medications and were currently taking 3 (0–5). Difference in seizure reduction between CBD and placebo emerged on Day 6 (titrated dose, 15 mg/kg/day) and became nominally significant ( p < .049) by Day 10. Separation between placebo and CBD in ≥50% responder rate also emerged by Day 10. Onset of AEs occurred during the first 2 weeks of the titration period in 61% of patients (CBD25, 61%; CBD50, 67%; placebo, 54%). In patients with an AE, resolution occurred within 4 weeks of onset in 42% of placebo and 27% of CBD patients and by end of trial in 78% of placebo and 51% of CBD patients. Significance: Onset of treatment effect occurred within 6–10 days. AEs lasted longer for CBD than placebo, but the most common (diarrhea, decreased appetite, and somnolence) resolved during the 16‐week trial in most patients.